Concepções de ensino de teclado eletrônico: um estudo de caso com professores do curso técnico do Conservatório Estadual de Música Lorenzo Fernândez - Scarcela, Samuel Naamã (2023)
This work aims to understand the conceptions of teachers of technical teaching of electronic keyboard of the State Conservatory of Music Lorenzo Fernandez on the teaching of the instrument. The theoretical reference of the research addresses the thought of the teacher (SACRISTAN, GOMEZ, 1987; BRAZ, 2007) and the reflective teacher (ALARCÃO, 2011; HARTMAN, 2015), showing aspects that can be part of the construction of the conceptions of teachers, directly influencing their teaching practice. The method used is the case-study (YIN, 2015) and the data collection consisted of conducting semi-structured interviews and analysis of the guiding documents of keyboard teaching in the conservatory (GIL, 2002). The results point to similar conceptions among teachers about the definition of the instrument, its main feature as accompanying instrument and the importance of mastering some content to form a professional keyboardist.